2015
DOI: 10.1016/j.prevetmed.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Factors likely to influence the adoption of targeted selective treatment strategies by sheep farmers in Western Australia

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…These reports concluded on additional barriers, which in turn were more adoption specific, such as complexity of the new GIN control approaches and their compatibility with the current approach, time requirements, and the ability to trial the proposed management practices ( 43 , 58 ). Moreover, the awareness of such new control approaches was associated with concerns on AR, previous experience with diagnostics and the consultation of professional advisers regarding worm control ( 59 ).…”
Section: Farmers' Adoption Of Sustainable Controlmentioning
confidence: 99%
“…These reports concluded on additional barriers, which in turn were more adoption specific, such as complexity of the new GIN control approaches and their compatibility with the current approach, time requirements, and the ability to trial the proposed management practices ( 43 , 58 ). Moreover, the awareness of such new control approaches was associated with concerns on AR, previous experience with diagnostics and the consultation of professional advisers regarding worm control ( 59 ).…”
Section: Farmers' Adoption Of Sustainable Controlmentioning
confidence: 99%
“…When purchasing a flukicide, respondents relied heavily on a single selection method (59%), of which 45% selected based on advice and 14% on previous use (Figure 6B). Cornelius et al (39) found that whoever sheep farmers sort advice from significantly influenced what other control methods were used on-farm. Farmers who relied on professionals (e.g., private veterinarians, government veterinarians, or private consultants) were more likely to use diagnostics to inform decision-making, test for resistance, drench less, and be aware of IPM.…”
Section: Flukicide Administrationmentioning
confidence: 99%